PHARMACOLOGICAL EVALUATION OF DIURETIC ACTIVITY OF ETHANOLIC EXTRACT OF HIBISCUS ROSA SINENSIS FLOWERS IN RATS - KAUR, RAVINDER; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the diuretic activity of the ethanolic extract of Hibiscus rosa-sinensis flowers in albino rats. Methods: The study used the Lipschitz test to assess diuretic activity in rats divided into four groups: control, standard (Frusemide 10 mg/kg), and test groups receiving extract doses of 200 mg/kg and 400 mg/kg. Urine was collected from all rats placed in metabolic cages, with parameters such as urine volume, pH, and concentrations of sodium, potassium, and chloride measured over 5 to 24 h. Results: The ethanolic extract significantly increased urine output and the excretion of sodium, potassium, and chloride at both tested doses, with the higher dose showing effects comparable to the standard diuretic Frusemide. No significant alteration in urine pH was observed. Conclusion: The ethanolic extract of Hibiscus rosa-sinensis flowers demonstrated dose-dependent diuretic activity and elevated electrolyte excretion, supporting its potential as a safe, orally active diuretic agent for further pharmacological research